A gene trap transposon eliminates haematopoietic expression of zebrafish Gfi1aa, but does not interfere with haematopoiesis. - Thambyrajah, Roshana Sutharshini; Ucanok, Deniz; Jalali, Maryam; Hough, Yasmin; Wilkinson, Robert Neil; Moore, Chris; Gering, Martin (Elsevier, 2016)
A transposon-mediated gene trap screen identified the zebrafish line qmc551 that expresses a GFP reporter in primitive erythrocytes and also in haemogenic endothelial cells, which give rise to haematopoietic stem and progenitor cells (HSPCs) that seed sites of larval and adult haematopoiesis. The transposon that mediates this GFP expression is located in intron 1 of the gfi1aa gene, one of three zebrafish paralogs that encode transcriptional repressors homologous to mammalian Gfi1 and Gfi1b proteins. In qmc551 transgenics, GFP expression is under the control of the endogenous gfi1aa promoter, recapitulates early gfi1aa expression and allows live observation of gfi1aa promoter activity. While the transposon integration interferes with the expression of gfi1aa mRNA in haematopoietic cells, homozygous qmc551 fish are viable and fertile, and display normal primitive and definitive haematopoiesis. Retained expression of Gfi1b in primitive erythrocytes and up-regulation of Gfi1ab at the onset of definitive haematopoiesis in homozygous qmc551 carriers, are sufficient to allow normal haematopoiesis. This finding contradicts previously published morpholino data that suggested an essential role for zebrafish Gfi1aa in primitive erythropoiesis.